The Influence of Job Satisfaction on The Loyalty of Millennial Employees in Batam City with Work–Life Balance As A Moderating Variable - Budi, Rafi Putra; Trinanda, Okki (Human Resource Management Studies, 2025)
This study aims to analyze the effect of job satisfaction on the loyalty of millennial employees in Batam City and examine the moderating role of work-life balance. This research uses a quantitative approach with the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS). The sample consisted of 120 millennial employees working in Batam City. The results showed that job satisfaction has a positive and significant effect on employee loyalty. Work-life balance also has a positive and significant effect on employee loyalty and strengthens the relationship between job satisfaction and loyalty. These findings emphasize the importance of promoting a healthy work-life balance to enhance employee loyalty.